2013
DOI: 10.1063/1.4817023
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of radiation emitted from planar wire arrays

Abstract: International audienceThe planar wire array (PWA) is a promising load for new multi-source inertial confinement fusion (ICF) hohlraums [B. Jones et al. Phys. Rev. Lett. 104 125001 (2010)]. The hohlraum radiation symmetry is an important issue for ICF. It was found that extreme ultraviolet and sub-keV photon emission from PWAs may have considerable anisotropy in the load azimuthal plane. This experimental result is obtained on the UNR 1–1.7 MA Zebra generator. The time-dependent anisotropy effect is detected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A simplified hohlraum had the inner (FIG.6a). The highest yield/p e shown that m mulation has de ohlraum design lso, VisRad co [5] (typical ra additional Zebr th modified V y of the T R dis timated to be ut shields. Alto erent spectral r s (FIG.4b) at such ssfully e to Al IG.6b).…”
Section: Demonstration Of Equally Redistributed Currents and The Syncmentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified hohlraum had the inner (FIG.6a). The highest yield/p e shown that m mulation has de ohlraum design lso, VisRad co [5] (typical ra additional Zebr th modified V y of the T R dis timated to be ut shields. Alto erent spectral r s (FIG.4b) at such ssfully e to Al IG.6b).…”
Section: Demonstration Of Equally Redistributed Currents and The Syncmentioning
confidence: 99%
“…PWA turned out to be an effective radiator [2][3][4]. Compact, mm-scale, double-PWA (DPWA) and triple-PWA (TPWA) have demonstrated: larger resistive energy (>30 kJ/cm) and power (> 1TW/cm) gain [3], highest yield current scaling (I 1.8÷2 ) [3] among all loads tested at University-scale machines, anisotropy of power/yield dependent on wires' rows [5], and the possibility of radiation pulse shaping [6]. Planar foil liner (PFL) source (a promising alternative source to wire arrays [4]) has also shown yields which are close to the one of PWA, but with better axial Te and Ne gradients [4].…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of several important problems in the realization of the new hohlraum design has already been achieved. The possibility of PWAs x-ray pulse shaping was demonstrated [4,5], the anisotropy of PWA radiation output was studied [5], the maximizing of PWA radiation yield and power while keeping mm-scale source dimensions have been shown [5,6]. Recently, using a simplified compact hohlraum design (without capsule/target and tailored shine shields) equal current redistribution in several magnetically decoupled Z-pinch PWAs driven in parallel without radiation yield and power loss was achieved [7].…”
mentioning
confidence: 99%
“…The uniformity of the distribution of T R on the target surface was improved significantly with the application of tailored shine shields between the sources and a target ( Fig.1). Also, we are taking into account that the W DPWA is an anisotropic x-ray source [5] (typical ratio K=1.2 of power radiated along wire rows to one emitted orthogonal to planes was measured in our new Zebra tests) and maximum radiation is emitted in the direction parallel to the wire planes [5]. In this particular scheme a proper design of shine shields was applied to use the anisotropy to increase the radiation flux at the target surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation